Consequences of a sextuple-product identity - John A. Ewell (International Journal of Mathematics and Mathematical Sciences)
A sextuple-product identity, which essentially results from squaring the classical Gauss-Jacobi triple-product identity, is used to derive two trigonometrical identities. Several special cases of these identities are then presented and discussed.